Magnetic nanochain enabled microarray and microfluidic bioassays - Xiong, Qirong (2019)
There are growing demands for bioassay techniques that allow for rapid, multiplexed detection of a panel of targets with minimum specimen consumption. However, the devices of small size often present fundamental problems such as intrinsic poor liquid mixing and inefficient mass transfer across microfluidic channels and diffusion-limited on-surface assays, which create considerable obstacles to achieve rapid, ultrasensitive detection. Recently, we developed polydopamine (PDA) based strategy to produce one-dimensional (1-D) magnetic nanochains with rigid structure. The magnetic nanochains immediately align in a magnetic field and undergo synchronous rotation in response to a rotating magnetic field, making them ideal nanomixers to promote fast fluid mixing and analyte transport in microscale devices. Importantly, PDA not only serves as the scaffold to lock the nanochain structure, but also allows for convenient surface functionalization by means of spontaneous Michael addition and/or Schiff base reaction with nucleophilic thiol and amine groups. As such, the nanochains can be sequentially functionalized with specific antibody for target separation, thus realize multi-functional roles in bioassay.